WHITE PEOPLE’S RACIAL DISCRIMINATION IN KATHRYN STOCKETT’S THE HELP (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2018)
Abstract Racial discrimination occurs almost every day in the world. Generally, it can cause conflict and destroy the reconciliation of human beings. Racial discrimination can be defined as a different treatment given to certain individual or group. This action tends to differentiate human beings based on their races. Discrimination always has negative connotative issues in African America life and history. The discrimination towards African Americans happens when white people resist against black people. Moreover, the discrimination of the African Americans happens in many aspects of life.The purpose this study is to analyze how racial discrimination happened in the African American society; the racial discrimination upon black people by white people and how black people resist the racial discrimination in Kathryn Stockett’sThe Help.The racial discrimination which had been done by white people is the main topic for this research. It is based on the phenomenon of discrimination which happened in the society. The racial discrimination in the story shows how white people underestimate black people in terms of housework chores, education, and issues on racism or skin colors. Keywords : Racial Discrimination, African American Abstrak Diskriminasirasialhampirterjadisetiaphari di dunia. Padaumumnya, hal itu dapat menyebabkan konflik dan permusuhan antar manusia. Diskriminasi rasial dapat diartikan sebagai perlakuan menyimpang yang diberikan suatu individu atau kelompok kepada suatu kaum tertentu. Perlakuan ini ditujukan kepada suku atau ras tertentu. Diskriminasi selalu memiliki citra buruk dalam sejarah kehidupan bangsa Afrika Amerika.Diskriminasi rasial selalu terjadi ketikabangsa kulit putih menindas bangsa kulit hitam.Hal itu sendiri terjadi dalam beberapa aspek kehidupan.Tujuan dari skripsi ini adalah untuk mengalaisa bagaimana fenomena diskriminasi rasial terjadi dalam kehidupan bangsa Afrika Amerika :Diskriminasi rasial yang dilakuhkan oleh bangsa kulit putih kepada kulit hitam dalam novel The Helpkarya Kathryn Stockett.Diskriminasirasialmerupakantopikutamadalamperbahasan. Analisis yang dilakuhkanberdasarkanfenomenadiskriminasi yang terjadi di masyarakat.Diskriminasirasial yang dilakuhkan di masyarakatadalahsepertidalambidangkehidupandirumah, pendidikansertaisu negative tentangsukuataurastertentu. Kata Kunci :DiskriminasiRasial, AfrikaAmerika